The Educational Evolution in Germany, the study case: Primary Education (Grundschule) - Ashrafi, Ali (2021)
Primary education levels are called primary education, compulsory education, and public education. Nowadays, new research has shown that primary education plays an important role in the reduction of poverty and the realization of economic and social development programs. Therefore, the necessity of this research is to study the evolution of primary education and its influencing factors in Germany. Also, the primary organization and how to select the teacher education and primary curriculum will be examined. In this research, the research method is descriptive. The results showed that in the primary period of the German education system, politics, ideology, and ideas of educators have played an important role in the development of education and, as such, in primary education. As can be observed in the Weimar Republic, education was influenced by the political theories of democracy, and then, during the Nazis, was influenced by the ideology of Nazism and the superiority of the Nazi German race; during World War II and thereafter Was influenced by communist ideology and Marxist thoughts. In the new era, there have also been major reforms to eliminate the influence of these new educators' ideologies and educational ideas.